Pathogenesis of Hepatic Tumors following Gene Therapy in Murine and Canine Models of Glycogen Storage Disease - Kang, Hye-Ri (Mol Ther Methods Clin Dev, 2019)
Glycogen storage disease type Ia (GSD Ia) is caused by mutations in the glucose-6-phosphatase (G6Pase) catalytic subunit gene (G6PC). GSD Ia complications include hepatocellular adenomas (HCA) with a risk for hepatocellular carcinoma (HCC) formation. Genome editing with adeno-associated virus (AAV) vectors containing a zinc-finger nuclease (ZFN) and a G6PC donor transgene was evaluated in adult mice with GSD Ia. Although mouse livers expressed G6Pase, HCA and HCC occurred following AAV vector administration. Interestingly, vector genomes were almost undetectable in the tumors but remained relatively high in adjacent liver (p < 0.01). G6Pase activity was decreased in tumors, in comparison with adjacent liver (p < 0.01). Furthermore, AAV-G6Pase vector-treated dogs with GSD Ia developed HCC with lower G6Pase activity (p < 0.01) in comparison with adjacent liver. AAV integration and tumor marker analysis in mice revealed that tumors arose from the underlying disorder, not from vector administration. Similarly to human GSD Ia-related HCA and HCC, mouse and dog tumors did not express elevated α-fetoprotein. Taken together, these results suggest that AAV-mediated gene therapy not only corrects hepatic G6Pase deficiency, but also has potential to suppress HCA and HCC in the GSD Ia liver.